Analýza potřebvýznam a přínos analýzy potřeb pro zvýšení funkční gramotnosti - Koblížková, Andrea (Univerzita Pardubice, 2001)
The paper deals with the needs, its importance and benefits for foreign language competence. This category has been viewed as one of the aspects of functional literacy and cosidered and indicator of the total level of education in a particular society. A need analysis being both a premise and a tool of an appropriate syllabus design deserves a systematic approach. As language teaching should focus on learner's needs (both current and future) a reflective syllabus design is a natural necessity. The paper drawing from the method of determining different roles of language users aspires to come up with a more complex way of assessing the learnes' language needs. Obviously, the merit of such an approach rests not only upon inter-curricular cooperation but also upon closer collaboration of the spheres of theory and practice, i.e. the tertiary level of education and labour market requirements. To proof all these mutual relations the paper offers both a few basic statistical data highlighting the level of the Czech society compared to other European countries in term of education and results of a language needs analysis carried among the Faculty of Economics and Administration students at Pardubice University. Key words: functional literacy, inter-curricular relations, theory - practise cooperation, self - reflection, deductive reasoning, autonomous learning.
Keywords: Analýza; Potřeby; jazyková komunikace; gramotnost; Vzdělávání; výuka jazyků